Comprehensive and long-term surveys of COVID-19 sequelae in Japan, an ambidirectional multicentre cohort study: study protocol. Issue 1 (26th November 2021) - Nakagawara, Kensuke; Namkoong, Ho; Terai, Hideki; Masaki, Katsunori; Tanosaki, Takae; Shimamoto, Kyoko; Lee, Ho; Tanaka, Hiromu; Okamori, Satoshi; Kabata, Hiroki; Chubachi, Shotaro; Ikemura, Shinnosuke; et al.
Abstract : Introduction: The rapid spread of COVID-19 posed a global burden. Substantial number of people died of the disease in the acute phase of infection. In addition, a significant proportion of patients have been reported to suffer from post-acute phase symptoms, sequelae of COVID-19, which may negatively influence the quality of daily living and/or socioeconomic circumstances of the patients. However, no previous study has comprehensively and objectively assessed the quality of life of patients by using existing international scales. Further, evidence of socioeconomic consequences among patients with COVID-19 is scarce. To address the multidimensional issues from sequelae of COVID-19, evidence from comprehensive surveys beyond clinical perspectives is critical that investigates health, and social determinants of disease progression as well as socioeconomic consequences at a large scale. Methods and analysis: In this study, we plan to conduct a nationwide and comprehensive survey for the sequelae of COVID-19 in a total of 1000 patients diagnosed at 27 hospitals throughout Japan. This study will evaluate not only the health-related status of patients from clinical perspectives but also the Health-related Quality of Life (HRQoL) scores, socioeconomic status and consequences to discuss the sequelae of the disease and the related risk factors. The primary endpoint is the frequency of long-term complications of COVID-19 infection. The secondary endpoints are risk factors for progression to sequelae of COVID-19 infection. The study will provide robust and important evidence as a resource to tackle the issues from the sequelae of COVID-19 from the multi-dimensional perspectives. Ethics and dissemination: This trial was approved by the Keio University School of Medicine Ethics Committee (20200243, UMIN000042299). The results of this study will be reported at a society meeting or published in a peer-reviewed journal.